Proceedings of the International Conference on Advanced Intelligent Systems and Informatics 2016 - Hassanien, Aboul Ella; Shaalan, Khaled; Gaber, Tarek; Azar, Ahmad Taher; Tolba, Muhammad Fahmi (Springer, 2017)
This book gathers the proceedings of the 2nd International Conference on Advanced Intelligent Systems and Informatics (AISI2016), which took place in Cairo, Egypt during October 24-26, 2016. This international interdisciplinary conference, which highlighted essential research and developments in the field of informatics and intelligent systems, was organized by the Scientific Research Group in Egypt (SRGE) and sponsored by the IEEE Computational Intelligence Society (Egypt chapter) and the IEEE Robotics and Automation Society (Egypt Chapter). The book's content is divided into four main sections: Intelligent Language Processing, Intelligent Systems, Intelligent Robotics Systems, and Informatics.
Keywords: Expert systems (Computer science) -- Congresses.; Artificial intelligence -- Congresses.; elektronické knihy; electronic books